Child Labor: Cause, Consequence, and Cure, with Remarks on International Labor Standards - Basu, Kaushik (Journal of Economic Literature, 1999)
The paper brings together the abundant and somewhat anarchic literature on child labor, isolating its central findings and analytical insights. The investigation is especially directed at the micro economics of why child labor occurs and the sort of policy that is likely to succeed in eradicating it. The paper also outlines new directions for analyzing the dynamics of child labor, the possibility of “child-labor traps” and the circumstances in which voluntary contracts should be banned. Various arguments for and against declaring child labor illegal are examined. A final section explores the economics of international child labor standards.